PERAN LITERASI BUDAYA DAN LITERASI DIGITAL DALAM MENINGKATKAN MODERASI BERAGAMA MAHASISWA - Amseke, Fredericksen Victoranto (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2023)
Religious moderation among students is the attitude and perspective of students to understand and respect each other's diversity and differences between ethnic cultures, languages and religions in Indonesia to avoid conflict between religious communities and create balance and strengthen harmony in religious life. This research aims to determine the influence of cultural and digital literacy on students' religious moderation at the Kupang State Christian Institute. This research uses quantitative methods. The data collection tool uses a questionnaire. Participants in this research were 260 students from 11 study programs at the Kupang State Christian Religion Institute. The data analysis technique uses multiple regression analysis. The results of this research show that cultural and digital literacy has a positive and significant role in students' religious moderation with an R Square value of 58.7%. Cultural literacy contributed 31.9% and digital 26.8% to religious moderation.